Spontaneous imbibition of water in capillary tubes that contain viscous silicone oils and gas bubbles - Ioana Rasuceanu; Claudiu Patrascu (Scientific Reports)
Abstract We investigate the spontaneous capillary imbibition of water in tubes that contain a silicone oil slug. The capillary flow is studied as a function of the silicone oil slug’s viscosity, volume and position in the capillary tube. The system was found to advance with constant velocity on short distances, which can serve as a tool for estimating the effective surface tension. When the silicone oil is situated at an arbitrary distance from the tube’s entrance, the air gets trapped during water imbibition, creating a gas bubble. The latter starts flowing and the more viscous phase drains via a thin film deposited on the tube’s inner wall. The silicone oil slug is collected at the advancing interface separating the two immiscible liquids. Using a classical deposition law we develop an approximate model for the draining process of the silicone oil. The time of total liquid recovery can be approximated with satisfactory precision, especially for low-viscosity silicone oils.